Pendidikan Anak Berkebutuhan Khusus Gifted Atau Berbakat - Putri Rizky Amanda; Nurwahidah Nasution; Ade Nisfu Ramadhania (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Gifted children have different characteristics from children in general. Gifted children have very high general intelligence abilities, special talents in certain fields, high creativity in thinking, namely the ability to find new ideas, have outstanding leadership skills, and have special achievements in the arts or other fields. In addition, gifted children can also be shown from several characteristics such as early adulthood, a stronger urge to learn according to their own will, and show a great and obsessive interest in certain fields. This article uses a type of qualitative research with literature studies and literature review.